1984
DOI: 10.1139/p84-188
|View full text |Cite
|
Sign up to set email alerts
|

The infrared spectrum of CS

Abstract: The infrared emission spectrum of carbon monosulfide was observed as a sequence of vibration–rotation bands in the X1Σ+ state, with strong heads of the Δν = 2 sequence degraded to the red. Eight bands of 12C32S were identified, and bands corresponding to the isotope 12C34S were also observed. The most prominent band head, that of the (2–0) band, is at 2585 cm−1, with the other heads spaced approximately 26 cm−1 to smaller wavenumbers. Our data, taken with the Fourier transform spectrometer at the National Sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…By comparing the continuum emission at different and overlapping baselines between the two datasets it appears that they are in agreement at the level of the calibration accuracy (20-30%). Also, Our SMA continuum measurements (only) are in agreement with previous SMA observations at 305 GHz and 354 GHz by Chandler et al (2005) and Kuan et al (2004) taking into account the dif- a All spectroscopic data from CO and CS isotopologues available from the CDMS molecular line catalog (Müller et al 2001(Müller et al , 2005 through the Splatalogue (www.splatalogue.net, Remijan et al 2007) portal and are based on laboratory measurements and model predictions by Klapper et al (2003); Cazzoli et al (2002); Goorvitch (1994); Winkel et al (1984); Ram (1995); Burkholder et al (1987); Gottlieb et al (2003); Ahrens & Winnewisser (1999); Kim & Yamamoto (2003); Bogey et al (1982Bogey et al ( , 1981.…”
Section: Data Reductionsupporting
confidence: 87%
“…By comparing the continuum emission at different and overlapping baselines between the two datasets it appears that they are in agreement at the level of the calibration accuracy (20-30%). Also, Our SMA continuum measurements (only) are in agreement with previous SMA observations at 305 GHz and 354 GHz by Chandler et al (2005) and Kuan et al (2004) taking into account the dif- a All spectroscopic data from CO and CS isotopologues available from the CDMS molecular line catalog (Müller et al 2001(Müller et al , 2005 through the Splatalogue (www.splatalogue.net, Remijan et al 2007) portal and are based on laboratory measurements and model predictions by Klapper et al (2003); Cazzoli et al (2002); Goorvitch (1994); Winkel et al (1984); Ram (1995); Burkholder et al (1987); Gottlieb et al (2003); Ahrens & Winnewisser (1999); Kim & Yamamoto (2003); Bogey et al (1982Bogey et al ( , 1981.…”
Section: Data Reductionsupporting
confidence: 87%
“…As our line width was smaller than theirs, our measurements of the vibrational-rotational transitions of 12 C 32 S are included in Table 1(b) and the spectral fitting. In Tables S1(a)-S1(c) in Supplementary material are listed the vibrational-rotational transitions reported by Burkholder et al [16], by Ram et al [17] and by Winkel et al [15], respectively, that are included in the spectral fit. The reported microwave transitions are listed in Tables S1(d)-S1(f) in Supplementary material.…”
Section: Spectral Calibrationmentioning
confidence: 99%
“…Ahrens and Winnewisser [10] reported sub-millimeter-wave spectra of 12 C 32 S, 12 C 33 S, 12 C 34 S, 13 C 32 S, 13 C 33 S, 13 C 34 S and 12 C 36 S. The rotational transitions up to J = 23-22 included some of 12 C 32 S (v 6 16), 12 C 33 S (v 6 2), 12 C 34 S (v 6 8), 12 C 36 S (v 6 1), 13 C 32 S (v 6 5), 13 C 33 S (v = 0) and 13 C 34 S (v 6 2) in vibrationally excited states. Kim and Yamamoto [11] observed the J = 1-0 transition in vibrational states up to v = 39, 16, 7, and 9 for 12 C 32 S, 12 C 34 S, 12 C 33 S and 13 C 32 S, respectively; the J = 2-1 transition was observed for 12 C 32 S in vibrational states from 18 to 20. In 1977, Todd [12] reported vibrational-rotational bands v = 2-0 of 12 C 32 S and 12 C 34 S, recorded with a grating spectrometer with resolution 0.045 cm À1 ; 70 spectral lines were reported for 12 C 32 S and 31 for 12 C 34 S. Using a tunable diode-laser spectrometer, Todd and Olson [13] observed 115 vibrational-rotational transitions that were assigned to bands v = 1-0, 2-1, 3-2 and 4-3 of 12 1-0 of 12 C 34 S, 12 C 33 S and 13 C 32 S. Winkel et al [15] observed the Dv = 2 emission bands of 12 C 32 S and 12 C 34 S with v 00 up to 8 for 12 C 32 S. Using a Fourier-transform spectrometer at resolution 0.004 cm À1 , Burkholder et al [16] measured bands v = 1-0 of 12 C 32 S, 12 C 33 S, 12 C 34 S and 13 C 32 S and band 2-1 of 12 C 32 S. Ram et al [17] measured the Dv = 1 emission bands for 12 C 32 S up to v = 9-8 and J 00 up to 113 for band v = 2-1; they observed the emission from samples at high temperatures with a Fourier-transform spectrometer at resolution 0.01 cm À1 . To date, the vibrational-rotational spectra for transitions up to large v and J have been reported for only 12 C 32 S and 12 C 34 S. Here we report the observation of the vibrational-rotational bands of 13 C 32 S up to v = 5-4 using a Fourier-transform spectrometer at resolution 0.010 cm À1 ; we report also a separate observation of the vibrational-rotational bands of 12 C 32 S up to v = 7-6.…”
Section: Introductionmentioning
confidence: 97%
“…We use the CS linelist of Chandra et al (1995) in our computations, we do not believe that errors in this linelist contribute to the overprediction of the strength of CS features in our synthetic spectra. This CS linelist was calculated by using Dunham coefficients from Winkel et al (1984), and the dipole moment surface of Botschwina & Sebald (1985). Within the rigid rotor approximation, the rotational J = 0 → 1 transition dipole is equal to the permanent dipole moment, thus can be used as a rough check for the accuracy of intensity calculations.…”
Section: Comparison Of Synthetic Spectra With Observed Stellar Spectramentioning
confidence: 99%